Impact of Liquidity and Sales Growth on Company Value: A Case Study of Telecommunications Firms on the Indonesian Stock Exchange - Indra Riyana Rahadjeng; Melyani Melyani; Dian Mohamad Anwar; Ahmad Rafik; Isyana Emita; Wahyu Indrarti; Dian Indah Sari (Journal of Management and Informatics, 2025)
This study investigates the impact of liquidity and sales growth on company value within the Indonesian telecommunications sector from 2020-2024. Grounded in Signaling Theory, this research employs a quantitative panel data regression on a saturated sample of five IDX-listed firms. Using the Price-to-Book Value ratio as a proxy for company value, the analysis tests the influence of the Current Ratio (liquidity) and annual sales growth. The selected Fixed Effects Model shows that both liquidity and sales growth have significant positive effects, confirming that they serve as credible signals influencing investor valuation.